Analysis Factors Related to Implementation of Complete Basic Immunization in Work Area of Pengambiran Public Health Center in Padang 2017 - Ade Nurhasanah Amir; Eryati Darwin; Yuniar Lestari (Journal of Midwifery, 2018)
The role of a mother in the immunization program is very important, so their understanding of immunization is necessary, the behavior of a person or society about health is determined by knowledge, attitude, belief, tradition, work etc. from the person or society concerned. In addition, the availability of health care facilities, attitudes, behavior of health workers on the provision of health information will also support and strengthen the formation of health behaviors, This study aims to determine the factors that affect the provision of complete basic immunization, This study uses a combined research method between quantitative and qualitative.Sample for this study is 107 mother mother, while informant for qualitative study is Head of PuskesmasPengambiran Padang City, Responsible, Immunization Officer of Puskesmas and Kader which is in Working Area of PengambiranPublic Health in Padang City, The result of this study shown that family support is the most important factors in the implementation Complete basic immunization (p = 0.001). The results of the analysis revealed that the coverage of the implementation of complete basic immunization has not been successful because the lack of active role of cadres and health officers in community in informing immunization in depth. so that there is still a lack of understanding from mothers and families which has no family support in the implementation of complete basic immunization, it has not reached 95% target because the system implementation of complete basic immunization services that have not been optimal. It needs various efforts to improve the achievement of complete basic immunization coverage especially through optimizing the role and function of health and cadre officers and optimizing partnerships with various parties.